2022
DOI: 10.12790/ahm.22.0015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of renal dysfunction in free flap transfer for chronic wounds of the lower extremities

Abstract: Purpose: Free flaps play an important role in the reconstruction of chronic wounds in the lower extremities. Nonetheless, the use of free flaps for chronic wound reconstruction tends to be challenging. A considerable number of patients with chronic wounds have noteworthy medical histories, such as chronic kidney disease or end-stage renal disease (ESRD). This study aimed to determine the relationship between the success rate and complications of free flap surgery according to the degree of kidney disease from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A retrospective study was conducted by Hahn et al from 2011 to 2020. The study evaluated 67 patients who underwent free tissue transfer procedures for chronic wounds in the lower‐extremity region (Hahn et al, 2022). The flap failure rate in all patients was 9%, and major complications were experienced by 16 patients (23.9%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study was conducted by Hahn et al from 2011 to 2020. The study evaluated 67 patients who underwent free tissue transfer procedures for chronic wounds in the lower‐extremity region (Hahn et al, 2022). The flap failure rate in all patients was 9%, and major complications were experienced by 16 patients (23.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed a similar pattern of results, with one mortality case in the dialysis group, although the difference did not achieve significant level (7.7% vs. 0%, p = .085).A retrospective study was conducted byHahn et al from 2011Hahn et al from to 2020. The study evaluated 67 patients who underwent free tissue transfer procedures for chronic wounds in the lower-extremity region(Hahn et al, 2022). The flap failure rate in all patients was 9%, and major complications were experienced by 16 patients (23.9%).…”
mentioning
confidence: 99%
“…They had an immediate flap failure rate of 6% with an overall rate of post‐operative complications of 44% 11 . Hahn et al also looked at free tissue transfers for chronic wounds of the lower extremities and found a direct correlation between free flap failure and ESRD and renal transplantation patients, with a flap failure rate of 9% and a complication rate of 23.9% 12 . It is important to note that most of these patients were undergoing reconstruction for lower limb ischemia due to other medical co‐morbidities, most prevalently diabetes and peripheral vascular disease.…”
Section: Discussionmentioning
confidence: 99%